Product Markets and Labour Markets. - Nickell, S (1999)
The concern of this paper is whether monopoly power in the product market impacts badly on the performance of the labour market. There is strong evidence of the sharing of monopoly rents and of higher wages being associated with market power. It is not clear whether this is simply a union effect or whether it applies in the non-union sector. The balance of the evidence also suggests a negative relationship between product market power and productivity performance.